A clustering approach to analyse the environmental and energetic impacts of Atlantic recipes - A Galician gastronomy case study. (10th January 2023) - Cambeses-Franco, Cristina; González-García, Sara; Calvo-Malvar, Mar; Benítez-Estévez, Alfonso J.; Leis, Rosaura; Sánchez-Castro, Juan; Gude, Francisco; Feijoo, Gumersindo; Moreira, María Teresa
Abstract: The definition of the term gastronomy encompasses both the knowledge of food and its handling, preparation and consumption. Beyond a sense of cultural identity and tradition, gastronomy also represents a pole of tourist attraction. This is the case of Galicia, a region in north-western Spain. Within this framework, local dishes, which include distinctive elements of the Atlantic diet, have gained popularity. This research delves into the sustainability of 60 Galician recipes by performing a hierarchical cluster analysis to study their carbon footprint, the energy return on investment ratio and cost. The life cycle assessment methodology was followed to account for the carbon footprint and the energy return on investment ratio of the recipes. The scope was bounded to the cradle-to-fork phases through the life cycle: production of the ingredients, transport, and meal preparation. The functional unit selected was one serving of a Galician meal. The results suggest that the recipes could be classified into three main groups according to the presence of a greater or lesser amount of animal-based products. Cluster 1 comprises 10 meat recipes. Cluster 2 encompasses 31 recipes rich in fish with some vegetables and moderate consumption of red meat and dairy products. Cluster 3 includes 22 vegetable-based recipes. The higher the portion of animal products in the recipes (mainly red meat), the higher the costs and carbon footprint and the lower the energy return on investment ratio. Conversely, plant-based recipes tend to reduce greenhouse gases emissions and increase cost competitiveness and energy efficiency indicators. Based on this study, the food service could promote eco-labelling that support and certify restaurant menus. This research could also provide transformative climate education for sustainable food for consumers, giving advice to improve food-based dietary guidelines in Spain. Highlights: Analysis of the carbon footprint, energy consumption and cost of Atlantic recipes. Recipes can be classified into three hierarchical dietary clusters. Cluster 1 comprises meat recipes with low energy return on investment ratio and high carbon footprint and economic cost. Cluster 2 comprises recipes rich in fish with vegetables and moderate meat. Cluster 3 includes low-cost and low-carbon vegetable-based recipes.